2017
DOI: 10.1016/j.ihj.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thrombolytic therapy on the patterns of post myocardial infarction ventricular septal rupture

Abstract: ObjectivesVentricular septal rupture (VSR) is a rare but feared complication after myocardial infarction (MI). The objective of this study was to investigate the effects of thrombolytic therapy on the patterns of VSR following MI.Methods30 consecutive patients admitted to a single tertiary level cardiac hospital with a diagnosis of acute MI and developed VSR in the hospital were included. The effect on thrombolytic therapy on the formation of VSR and its clinical outcome was studied.ResultsOut of 30 patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
1
5
0
1
Order By: Relevance
“…40 Furthermore, the median time to VSR formation post-MI was significantly shorter in patients receiving thrombolysis treatment than in those without thrombolysis treatment, and compared with late thrombolysis treatment, early thrombolysis treatment was associated with shorter median time to post-MI VSR formation. 41 Results of subgroup analyses showed that in the subgroup of patients with VSR, female gender, older age, and LAD involvement remained risk factors for CR. In the subgroup of patients with STEMI, the risk factors were female gender and older age.…”
Section: Original Research Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…40 Furthermore, the median time to VSR formation post-MI was significantly shorter in patients receiving thrombolysis treatment than in those without thrombolysis treatment, and compared with late thrombolysis treatment, early thrombolysis treatment was associated with shorter median time to post-MI VSR formation. 41 Results of subgroup analyses showed that in the subgroup of patients with VSR, female gender, older age, and LAD involvement remained risk factors for CR. In the subgroup of patients with STEMI, the risk factors were female gender and older age.…”
Section: Original Research Discussionmentioning
confidence: 94%
“…The timing of thrombolytic therapy for AMI has been shown to be associated with CR risk, with more prolonged time to treatment after MI associated with increasing risk (7 hours, OR=0.4; 11 hours, OR=0.93; 17 hours, OR=3.21) 40. Furthermore, the median time to VSR formation post-MI was significantly shorter in patients receiving thrombolysis treatment than in those without thrombolysis treatment, and compared with late thrombolysis treatment, early thrombolysis treatment was associated with shorter median time to post-MI VSR formation 41…”
Section: Discussionmentioning
confidence: 95%
“…These interventions are important to stabilize the patient's condition in preparation for further repair. If pharmacological therapy is not effective, Intra-aortic balloon pump (IABP) should be used [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intra-aortic balloon pump (IABP) should be considered if pharmacological therapy fails to achieve hemodynamic stability. 12,15 IABP can support these patients by lowering afterload and also decreasing the shunt and at the same time facilitating coronary perfusion.…”
Section: Discussionmentioning
confidence: 99%